Molecular cloning, expression analysis and localization pattern of the MST family in grass carp (Ctenopharyngodon idella). Issue 76 (May 2018) - Chu, Pengfei; He, Libo; Xiong, Lv; Luo, Lifei; Huang, Rong; Liao, Lanjie; Li, Yongming; Zhu, Zuoyan; Wang, Yaping
Abstract: The mammalian sterile 20-like (MST) family, which belongs to the serine/threonine protein kinase superfamily, has five members that can be found in mammals: STK3 (also called MST2), STK4 (MST1), STK24 (MST3), STK25 (YSK1 or SOK1), and STK26 (MST4). The MST kinases have key roles in apoptosis, immune regulation, inflammatory responses, cancer, and cell proliferation in mammals, whereas the roles and transcriptional regulatory mechanism of these kinases in teleost fish are still unclear. In this study, four STK genes ( CiSTK3, CiSTK24, CiSTK25, and CiSTK26 ) were cloned and analyzed in grass carp ( Ctenopharyngodon idella ). All four STK genes were broadly expressed in the examined tissues, while their relative expression levels differed. In addition, after exposure to the grass carp reovirus, mRNA expression levels of the four STK genes were altered to different levels in the immune organs, and the levels were dramatically altered in the blood. Subcellular localization indicated that all four STK proteins were localized in the cytoplasm of transfected cells. Moreover, bimolecular fluorescence complementation analysis revealed that mouse protein-25 could interact with CiSTK3, CiSTK24, CiSTK25, and CiSTK26 independently in grass carp. Thus, our findings provide new insights for understanding the functions of the MST family in teleosts. Highlights: We cloned and analyzed CiSTK3, CiSTK24, CiSTK25, and CiSTK26 from C. idella. We determined the expression pattern and transcriptional regulation of the genes. The genes have key roles in immune regulation after GCRV infection. Mouse protein-25 was detected to interact independently with CiSTK3, CiSTK24, CiSTK25 and CiSTK26.